Modelling of Sulfur Dioxide Removal by Seawater in a Flue Gas Desulfurization Absorber - Dewi, Kania; Andreasen, Anders; Ediansjah, Addina Shafiyya (Journal of Engineering and Technological Sciences, 2024)
Although Indonesia has set a target for increasing the use of renewable energy for electricity generation, the use of coal as a source of energy will still dominate at least until 2040. Sulfur dioxide (SO2) along with other gases and particulates released from the use of coal in coal-fired power plants (CFPPs) may cause air pollution. The use of seawater, an abundant source of absorbent in a maritime country such as Indonesia, in flue gas desulfurization (SWFGD) absorbers, is an economical option for treating SO2 in an absorption tower compared to other alkaline chemicals, e.g. limestone (CaCO3) or magnesium hydroxide (Mg(OH)2). A model, which correlates the equilibrium of the reaction with the salinity of the absorbent, was developed to predict the sulfur dioxide scrubbing process inside an SWFGD absorber. The simulation also took into account the mass and energy balance during the scrubbing process. The calibration using field SWFGD data showed a good correspondence between field data and modelling results.